2001
DOI: 10.1053/jlts.2001.29167
|View full text |Cite
|
Sign up to set email alerts
|

Long-term management of the liver transplant patient: Diabetes, hyperlipidemia, and obesity

Abstract: Key Points 1. As long-term survival improves after liver transplantation, cardiovascular complications are emerging as a major cause of late morbidity and mortality. It seems reasonable to correct the potentially reversible cardiovascular risk factors of diabetes, hyperlipidemia, and obesity, in addition to hypertension. 2. The results of liver transplantation in diabetics are acceptable in terms of morbidity, mortality, and prevalence of posttransplant diabetes, but the poor outcomes described in some series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
3
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 62 publications
(99 reference statements)
1
90
3
2
Order By: Relevance
“…In addition, our in vivo studies showed that inhibiting the mTOR pathway leads to a decrease in obesity. These novel observations however conflict with that of prolonged use of rapamycin in humans which is associated with excessive weight gain, severe hyperinsulinemia, insulin resistance, and hyperglycemia in organ transplant patients (45,50,51). Taken together, these observations indicate that a considerable adverse effect of RAPA may exist for patients in a cachexia condition.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…In addition, our in vivo studies showed that inhibiting the mTOR pathway leads to a decrease in obesity. These novel observations however conflict with that of prolonged use of rapamycin in humans which is associated with excessive weight gain, severe hyperinsulinemia, insulin resistance, and hyperglycemia in organ transplant patients (45,50,51). Taken together, these observations indicate that a considerable adverse effect of RAPA may exist for patients in a cachexia condition.…”
Section: Discussioncontrasting
confidence: 41%
“…These endogenous molecules' association with food intake may work within the mTOR pathway or interact with each other in the hypothalamus (45). However, further investigation is necessary to determine the details of how these factors interact.…”
Section: Discussionmentioning
confidence: 99%
“…Weight gain after liver transplantation has been widely reported, with about two-thirds of patients becoming obese soon after transplant [17]. There is much debate as to the cause of this weight gain, but several factors, including immunosuppressive drugs and a return of normal diet and appetite have been suggested.…”
Section: Liver Transplant: General Considerationsmentioning
confidence: 99%
“…In addition, patients undergoing liver transplantation feel freed from pre-transplant restrictions dietary and no longer have anorexia. They also have a higher sense of well-being and anxiety to regain the weight lost while waiting for transplantation 15 . Still, it is likely that patients return to old eating habits; the contribution of a history of overweight has been widely described as a risk factor for excessive weight gain and obesity 8 Table 1 Table 1 Table 1 Table 1 Table 1 Incidence and prevalence of excess weight, overweight and obesity after liver transplantation.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…Also, they feel better and are able to feed in appreciable quantities. At the same time, they feel eager to regain the weight lost during the months of waiting for transplantation 14,15 , since 75% of them are malnourished during this period 16 . Moreover, many patients do not return to work after surgery 17 and those surviving for long periods have levels of daily physical activity significantly lower than the general population 4.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%